Implementation of Reward and Punishment in Forming Discipline Charachter Early Childhood - Tri Yuningsih, Titin; Sunaryo, Ilham (Lembaga Pengembangan Publikasi Ilmiah dan Buku Ajar, 2021)
According to the theory of Sr. Bondreward and punishment functions to influence positive responses or negative responses. The purpose of a positive response is to change someone's behavior for the better so that their good behavior will always repeat or increase. Meanwhile, the purpose of negative responses is to eliminate someone's bad behavior. Discipline is generally understood as personality and proper rules with certainty or personality that is gained from training such as, for example,